Une expérience de la SFI et du Groupe de la Banque mondiale pour mobiliser le secteur privé en faveur du développement - Philippe Le Houérou; Hans Peter Lankes (Fondation pour les études et recherches sur le développement international (FERDI), 2023)
– Private financial flows to Emerging Markets and Developing Economies (EMDEs) today are lower than in 2015, when both the UN's Addis Ababa Agenda for Action and the Paris Agreement were adopted - committing the world to financing the SDGs and reducing carbon emissions. Were the expectations simply unrealistic? How can we hope to measure up to the challenge of our generation?
Keywords: 330